Adequate Intake and Supplementation of B Vitamins, in Particular Folic Acid, can Play a Protective Role in Bone Health - Rondanelli, Mariangela; Tartara, Alice; Fossari, Federica; Vecchio, Viviana; Faliva, Milena A.; Naso, Maurizio; Perna, Simone; Nichetti, Mara; Peroni, Gabriella (Current Aging Science, 2022)
In vitro and animal model studies have shown that vitamin B (VB) deficiency has negative consequences on bone as a result of direct or mediated activity of hyperhomocysteinemia. However, there are still no precise indications regarding a possible VB role in order to maintain bone health. So, the aim of this narrative review was to consider state of the art correlation between VB dietary intake, blood levels and supplementation and bone health (bone mineral density (BMD), bone turnover markers and fractures risk) in humans. This review includes 29 eligible studies. Considering VB blood levels, the 14 studies considered have shown that low serum folate can be a risk factor for reduced BMD and fractures in the elderly, particularly women; no independent association was found for other VB. Studies that evaluate the relationship between VB dietary intake and BMD are only 2; one, conducted on 1869 women, demonstrated a positive effect of folate intake on BMD. Another demonstrated a dose-dependent inverse relationship between vitamin B6 dietary intake and risk of hip fracture, but only for 35298 female participants. Regarding the relationship between BV supplementation and bone health (9 studies with only VB and 4 with other nutrients), all studies that considered patients with hyperhomocysteinemia or with low folate blood levels, are in agreement in demonstrating that folate supplementation (500mcg- 5mg) is useful in improving BMD. In conclusion, a request for folate and homocysteine blood levels in elderly patients with osteopenia/osteoporosis is mandatory. For patients with hyperhomocysteinemia or with low folate blood levels, folate supplementation (500mcg-5mg) is crucial.
Keywords: intake